Hierarchy Needs of Investigation Journalist in Spotlight Movie: The Semiotics Study - Juniarti, Gita; Prathama, Nikolaus Ageng (Jurnal Ilmu Komunikasi, 2024)
Spotlight movie explains about investigation journalist activities on The Boston Globe office. Editor in chief of The Boston Globe interests in the case of childhood sexual abuse in the US. While the team investigates it, they encounter many obstacles on the field. They get the threat and intimidate from any parts. The key sources do not want to talk about the incident. They do not provide important data about this case. In the end, Spotlight team managed to uncover the truth. Their investigation was successful and also get a Pulitzer award. This research use hierarchy of needs theory to analyze the motivations of investigative journalist. The hierarchy of needs illustrates the level of a person’s needs, start from psychological needs; safety needs; love and belonging needs; self-esteem; and self-actualization. This research also uses Ferdinand de Saussure theory to analyze signs, signifiers and signified that indicate about fulfillment needed of humans. The findings of this study show that Spotlight journalist has reached the highest human needs, namely self-actualization. Investigation journalists have big motivation to occur the optimal work as a social warrior to reveal facts and uphold justice.